Psychedelic Resurgence, Spirituality and Psychological Disorders: Epistemological and Clinical Implications - Ferreira, Ana Sofia Machado; Facco, Enrico (Advances in Social Sciences Research Journal, 2025)
The scientific interest in spirituality has increased in recent years, paralleled by promising findings on the effects of spiritual experiences induced by psychedelics substances (PS), in the treatment of psychiatric disorders. However, these experiences may also bring challenges, depending on a variety of non-pharmacological variables. This article argues that an undiscerning use of PS to induce spiritual experiences, may facilitate the development of psychospiritual pathology, of which spiritual bypassing is a common example. This conclusion is based on a combination of three arguments: a) the ability of PS to trigger transcendental phenomenology; b) the unfamiliarity of the ruling mechanistic-reductionist scientific paradigm with the nature and implications of spirituality; c) the influence of New Age beliefs promoting PS as vehicles for spiritual and psychological growth. Considering the common occurrence of transcendental phenomenology in psychedelic experiences, the use of appropriate tools for psychospiritual assessment and support should be encouraged. Bearing in mind that both Eastern and Western philosophical and spiritual traditions are living repositories of wisdom on how to address spiritual experiences, a possible solution points towards the selective incorporation of this millenary knowledge, from a secular, transcultural perspective, to support informed uses and practices in psychedelic research and therapy.